Beyond the Da Vinci Code : The Book that Solves the Mystery - Chandelle, Rene (London Bounty Books, 2006)
Mary Magdalene was the wife of Jesus Christ. When he was crucified a pregnant Mary Magdalene fled to France escaping persecution. In the country that offered her refuge, she gave birth to Sarah. Sarah's descendants became the Merovingion dynasty
Include Illustration
Keywords: Leonardo, da Vinci, 1452-1519 -- Da Vinci code (Brown, Dan) -- Church history